Seed-use behaviour of castor growers in Andhra Pradesh: SEED-USE BEHAVIOUR OF CASTOR GROWERS IN ANDHRA PRADESH - R VENKATTAKUMAR; M PADMAIAH; S V RAMANA RAO (Journal of Oilseeds Research, 2014)
The seed-use behaviour of castor growers in Andhra Pradesh was assessed through the response of 192 randomly selected castor growers in Mahabubnagar district of Andhra Pradesh in 2010. In order to understand the productivity potentials and profitability of castor cultivars as vital information necessary for interpreting the seed-use behaviour, secondary data pertaining to frontline demonstrations (FLDs) in castor for the period from 1997-98 to 2008-09 was analysed. Similarly, to understand the operational cost of castor cultivation (` /ha) and output price of castor (` /q) in Andhra Pradesh as support information, secondary data of FLDs in castor for the period from 1994-95 to 2007-08 were analysed. These analyses revealed that all the castor growers purchase seeds every year. Better performance of the improved cultivars over the locals was the reason for annual seed-purchase behaviour exhibited by all respondents. Peer group, input dealers, extension personnel of State Department of Agriculture (SDA) and progressive farmers were the information source for seed-purchase. Yield, seed weight and extent of seed filling were the major criteria for choosing the improved castor cultivars. Input dealers and SDA were the major sources of seed purchase. The seed source was selected based on the accessibility of the source, timely availability of seeds, credibility of the source and adequacy of information about the improved cultivars. GCH-4 and Kranthi were the major castor cultivars used by the castor growers. Susceptibility of the improved cultivars to pest and diseases, lack of guarantee about the performance of the cultivars at the time of seed purchase, lack of awareness about the new cultivars and costliness of the seeds of improved cultivars were the major constraints perceived in use of purchased seeds. Implicative strategies were suggested, based on the results of the study to improve the seed-use behaviour of castor growers in Andhra Pradesh.